Pengembangan Petunjuk Praktikum Kimia Bahan Alam Tentang Ekstraksi dan Identifikasi Senyawa Flavonoid dari Brokoli dan Kale - Wahida Shofyatun Nufusita; I Nyoman Loka; Yayuk Andayani (FKIP University of Mataram, 2026)
This research aimed to produce a natural products chemistry laboratory guide and to determine the feasibility based on validity and practicalit. This research was an experimental samples used in this research were 50 g broccoli and 50 g of fresh kale leaves. The subjects as sources of validity and practicality data were two lectures as expert validators and 18 students of the Chemistry Education study Program in the seventh semester of the 2021/2022 academic year for the practicality test of the laboratory guide, who were determined using purposive sampling tehnique and whose data were collected using a questionnaire technique. The experimental data were analyze qualitatively and showed the presence of flavonoid compounds. The development dara of laboratory guide in the form of validity data were analyzed using the Aiken’s V formula and percent of agreement. From the analysis, an Aiken’s V value of 0.92 was obtained, which is included in the very valid category. In additional, a percent of agreement value of 0.93 indicates a very high level of agreement among the raters. Based on the practicality test result, a value of P= 90% was obtained, which indicates that the laboratory guide is very practical. Based on these result, it can be concluded that the developed laboratory guide is caterorized as very feasible and very practical.